Costs of air quality regulation - Randy A. Becker; John Vernon Henderson (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper explores some costs associated with environmental regulation. We focus on regulation pertaining to ground-level ozone (O3) and its effects on two manufacturing industries — industrial organic chemicals (SIC 2865-9) and miscellaneous plastic products (SIC 308). Both are major emitters of volatile organic compounds (VOC) and nitrogen oxides (NOx), the chemical precursors to ozone. Using plant-level data from the Census Bureau's Longitudinal Research Database (LRD), we examine the effects of regulation on the timing and magnitudes of investments by firms and on the impact it has had on their operating costs. As an alternative way to assess costs, we also employ plant-level data from the Pollution Abatement Costs and Expenditures (PACE) survey. Analyses employing average total cost functions reveal that plants' production costs are indeed higher in (heavily-regulated) non-attainment areas relative to (less-regulated) attainment areas. This is particularly true for younger plants, consistent with the notion that regulation is most burdensome for new (rather than existing) plants. Cost estimates using PACE data generally reveal lower costs. We also find that new heavily-regulated plants start out much larger than less-regulated plants, but then do not invest as much. Among other things, this highlights the substantial fixed costs involved in obtaining expansion permits. We also discuss reasons why plants may restrict their size.
Keywords: D2; H73; L5; L6; Q25; 330; Environmental regulation; costs; investment; plant size; Umweltkosten; Luftreinhaltung; Investitionsentscheidung; Theorie